1995
DOI: 10.1006/qres.1995.1003
|View full text |Cite
|
Sign up to set email alerts
|

Grain Size of Quartz as an Indicator of Winter Monsoon Strength on the Loess Plateau of Central China during the Last 130,000 Yr

Abstract: The Chinese loess-paleosol sequence constitutes an important record of variations in Asian monsoon climate over the past 2.4 myr. Magnetic susceptibility of loess and paleosols has been used as a proxy for summer monsoon intensity, while median grain size has been regarded as a measure of the strength of winter monsoon winds that were responsible for most of the dust transport. However, median grain size is only an approximate index of winter monsoon strength because both paleosols and loess have been modified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
240
1
4

Year Published

1999
1999
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 476 publications
(256 citation statements)
references
References 23 publications
11
240
1
4
Order By: Relevance
“…The bathymetric contour of -80 m in the East China Sea is illustrated to show the paleo-position of the coastline during glacial stages. Modern summer monsoon limit (Xiao et al, 1995) is also shown.…”
Section: Geological Setting Of the Studied Sitementioning
confidence: 92%
“…The bathymetric contour of -80 m in the East China Sea is illustrated to show the paleo-position of the coastline during glacial stages. Modern summer monsoon limit (Xiao et al, 1995) is also shown.…”
Section: Geological Setting Of the Studied Sitementioning
confidence: 92%
“…7; core 17940), values that are characteristic of loess deposits in Central China (Xiao et al, 1995;Porter and An, 1995). Near 18,000 14 C years (940-890 cm c.d.…”
Section: Records Of Continental Wetness and Ariditymentioning
confidence: 98%
“…To investigate past winter monsoon activity physical grain size and sedimentation rates (SR) are analysed; both of these are expected to increase as the intensi¢cation of the winter monsoon results in more vigorous westerly air movement. A variety of grain size measurements from sites across the loess plateau have been successfully utilised in the reconstruction of past winter monsoon levels at both orbital scales (Ding et al, 1994(Ding et al, , 1995(Ding et al, , 1999Shackleton et al, 1995;Xiao et al, 1995) and sub-orbital scales Chen et al, 1997).…”
Section: The East Asian Monsoon System and Loess Deposits Of Northernmentioning
confidence: 99%